Multi-Region Genomic Landscape Analysis for the Preoperative Prediction of Lymph Node Metastasis in Esophageal Carcinoma - Lin, Shaofeng; Chen, Yanping; Wang, Jianchao; Cai, Yibin; Chen, Xiaohui; Chen, Yuanmei; Shi, Yi; Chen, Gang; Zhu, Kunshou (Frontiers in Genetics, 2022)
Objective：Esophageal cancer is an aggressive malignant tumor with 90 percent of the patients are prone to recurrence and metastasis. Although recent studies have identified some potential biomarkers, these biomarkers' clinical or pathological significance was still unclear. Therefore, it is urgent to further identify and study novel molecular changes of esophageal cancer. It has positive clinical significance to identify a tumor-specific mutation in patients after surgery for an effective intervention to improve the prognosis of patients. Methods: In this study, we performed whole-exome sequencing (WES) on 33 tissue samples from 6 esophageal cancer patients with lymph node metastasis, compared the differences of the genomic map and evolutionary map in different tissues, and then performed the pathway enrichment analysis on non-synonymous mutation genes. Finally, we sorted out the somatic mutation data of all patients to analyze the subclonality of each tumor. Results: There were significant differences in somatic mutations between the metastatic lymph nodes and the primary lesions in the six patients. The clustering results of pathway enrichment indicated that the metastatic lymph nodes had certain commonalities. Tumors of the cloned exploration results illustrated that the five patients showed substantial heterogeneity. Conclusion: WES technology can be used to explore the differences in regional evolutionary maps, heterogeneity and detect patients' tumor-specific mutations. In addition, a thorough understanding of tumor heterogeneity ontogenesis and system development, thereby further found new molecular changes in the EC, can improve the prognosis of patients with EC and provide a valuable reference for the diagnosis of patients.